Research of current situation and countermeasures of campus network ecosystem - Xianghui Zhu; Fengqi Xie (2012 2nd International Conference on Consumer Electronics, Communications and Networks, 2012)
In order to look into the current situation of campus network ecosystem and establish a sound system, we carry out a survey about Wuhan Institute of Technology and find that there are some problems in university management and students themselves. This paper aims to put forward some suggestions for optimizing campus network ecosystem from the view of ecology. They are divided into five parts: network facilities, network information, network subject, network culture and network systems.